2004
DOI: 10.1111/j.1365-2265.2004.02000.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of GH replacement in adult GH‐deficient patients: changes in body composition without concomitant changes in the adipokines and insulin resistance

Abstract: These data demonstrate GH replacement in adult subjects with GHD is effective in changing body composition and restoring IGF-I levels over a 12-month period; however, in our study, these changes were not accompanied by changes in adipokine levels or beneficial effects on plasma lipids or insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 67 publications
8
56
2
Order By: Relevance
“…The favourable effects of GH replacement were independent of the parameters of obesity and can thus be considered as self-determining. This finding supports previous findings from the literature (29,30), although it conflicts with some other data (23,24). Moreover, administration of GH changed all studied variables in a similar way in nearly all groups, suggesting that the favourable response to GH was maintained independent of the presence or degree of obesity.…”
Section: Discussioncontrasting
confidence: 47%
“…The favourable effects of GH replacement were independent of the parameters of obesity and can thus be considered as self-determining. This finding supports previous findings from the literature (29,30), although it conflicts with some other data (23,24). Moreover, administration of GH changed all studied variables in a similar way in nearly all groups, suggesting that the favourable response to GH was maintained independent of the presence or degree of obesity.…”
Section: Discussioncontrasting
confidence: 47%
“…In support of this, Hana et al found an increase in lean and a decrease in fat mass in 17 patients with GHD treated over 1 year, without a concomitant change in adipokines and insulin resistance (53). Opposite to this, a randomised, double-blind, placebo-controlled multicentre study of 166 patients with GHD treated over 1 year also found a decrease in fat and increase in lean body mass, but in this case with a concomitant reduction in total and LDL-cholesterol (54).…”
Section: Discussionmentioning
confidence: 69%
“…Cardiovascular risk factors described in this population include altered body composition with truncal adiposity, detrimental changes in lipid profile, insulin resistance and impaired exercise capacity, among others (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%